The Relationship Between Maternal Employment Status and Speech Delay in Early Childhood: A Case-Control Study from a Private Pediatric Clinic in Malang, Indonesia - Nathania Lisna Ardelia; Ayling Sanjaya; Anna Lewi Santoso (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Speech delay is a common developmental concern in early childhood, affecting cognitive, social, and emotional domains. Maternal employment has been hypothesized to influence speech development, potentially due to reduced parent–child interaction. However, current evidence remains inconclusive, particularly in low- and middle-income countries. This study aimed to evaluate the association between maternal employment and speech delay in children aged 0–6 years in Malang, Indonesia. A case–control study was conducted from January to March 2025 at a private pediatric clinic in Malang City, Indonesia. A total of 60 children were recruited through consecutive sampling and categorized into two groups: 30 children with speech delay (cases) and 30 with typical speech development (controls). Maternal employment status and relevant sociodemographic data were collected using structured questionnaires. Speech development was assessed using the validated Kuesioner Pra Skrining Perkembangan (KPSP). Statistical analysis was performed using the Chi-square test, with significance set at p < 0.05. Of the total participants, 27 mothers (45.0%) were employed. Among children of employed mothers, 48.1% had speech delay, compared to 51.5% among children of non-employed mothers. The association between maternal employment and speech delay was not statistically significant (χ² = 0.07; p = 0.795). No significant association was found between maternal employment and speech delay. These findings suggest that emphasis should shift from employment status to enhancing the quality of parent–child interaction and promoting early developmental support in diverse family contexts.